EFFICACY OF Curcuma longa, Withania somnifera, Ginkgo biloba ithania somnifera, Ginkgo biloba IN CURING DEMENTIA: A SYNERGISTIC PHARMACOTHERAPY - KAMANA SINGH; PRABHA ARYA; NISHA VASHISHTA; AKANKSHA RAJPATI; ANUSHKA RAINA; HARVIN SIAG; VARSHA BAWEJA (The Bioscan, 2024)
Dementia, a neurodegenerative disease, manifests as a gradual deterioration in cognitive function and memory. Given the substantial side effects associated with current dementia therapeutics, this review aims to identify traditionally used plants that could potentially provide a lasting remedy without causing much side effects. Specifically, the review delves into the compatibility of three such plants—Curcuma longa, Withania somnifera, and Ginkgo biloba—examining their pharmacotherapeutic and neuroprotective efficacy at different stages of neuropathological mechanism cascade. Data of various clinical trials, using these plant products or their active constituents, done so far is also compiled and compared. This data holds the potential to further investigate the feasibility of employing these plants or their active constituents in a synergistic manner for the treatment of dementia patients. This review work can further contribute to standardizing the drug composition and determining its effective dosage.